(untitled) - Kagawa, Toyohiko (Chicago, 1929)
This book expresses a faith like that. It traces love up through lower unconscous statges in forms of mutual aid and the sacrifice of the self for the group to the joyous, radiant, conscious dedication of the personal life for the sake of others, flowering at its highest and holiest culmination in the Great Galilean, through whom God's character as grace and love at last stands revealed in its full glory,...
Keywords: Love; Religious aspects,Christianity